Porous nanofiber emulsion separation membrane with bionic structure and preparation method of porous nanofiber emulsion separation membrane
By introducing bionic structure porous nanofibers into the electrospinned oil-water emulsion separation membrane, the combination effect of spindle and porous structure is used to solve the problem that the penetration flux and separation efficiency are difficult to synchronize, and efficient emulsion separation and high penetration are achieved quantity.
Patent Information
- Application Number
- CN202411413828.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-02-14
AI Technical Summary
The problem of the difficulty in synchronizing the penetration flux and separation efficiency of the existing electrospun oil-water emulsion separation membrane.
A bionic structure porous nanofiber emulsion separation membrane is adopted. Its spindle structure causes the emulsified oil to move in a direction and spontaneously coalesce under the action of Laplace pressure differential, combining the excellent water absorption capacity and capillary action of the porous structure, significantly improving the permeability flux.
It has achieved efficient emulsion separation effect and high permeability flux, with separation efficiency up to more than 99.3%, and flux up to more than 6000L m-2h-1.
Smart Images

Figure CN119425404A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a bionic structure porous nanofiber emulsion separation membrane and a preparation method thereof, belonging to the technical field of functional micro-nano fiber materials. Background Art
[0002] Oily wastewater pollution caused by industrial emissions and oil spills has caused serious harm to the health of animals and plants and the ecological environment. Traditional oil-water separation technologies (such as skimming, flotation, centrifugation, sedimentation, etc.) are mostly only suitable for separating oil-water mixtures. For the separation of oil-water emulsions, the efficiency is low and the energy consumption is high.
[0003] In recent years, membrane separation technology has attracted great attention from researchers due to its advantages such as easy operation, low cost and low energy consumption. Among them, electrospun nanofiber membranes are often used to prepare superhydrophilic-underwater superoleophobic emulsion separation membranes due to their many advantages such as high porosity, good pore connectivity and large specific surface area. The separation principle is mainly based on wettability differences and pore size screening, which effectively separates emulsified oil from water. The hydrophilicity allows water to pass quickly, and the underwater oleophobicity has a high repulsion to oil. However, the existing electrospun oil-water emulsion separation membranes often have the problem of difficulty in simultaneously improving flux and separation efficiency. Therefore, it is urgent to develop an oil-water emulsion separation membrane with high flux and high efficiency. Summary of the invention
[0004] [Technical issues]
[0005] The invention solves the problem that the permeation flux and separation efficiency of the oil-water emulsion separation membrane in the prior art are difficult to be improved simultaneously.
[0006] [Technical solution]
[0007] In nature, the spindle knots on wet spider silk can transport and collect water droplets in a directional manner, which is mainly caused by the surface energy gradient and Laplace pressure difference. This directional movement can promote the coalescence of tiny droplets, which can easily move away from the solid surface under the action of gravity or buoyancy. Sponges have a very strong ability to absorb water due to their porous structure. The tiny pores provide a huge surface area, and water can be absorbed into the pores of the sponge through capillary action. This porous structure with capillary effect can significantly improve the transport of water.
[0008] The present invention provides a bionic porous nanofiber emulsion separation membrane and a preparation method thereof. The nanofiber membrane prepared by the present invention has a spindle knot imitating spider silk, which can make the emulsified oil in water move in a directional manner and spontaneously aggregate under the action of Laplace pressure difference, thereby achieving a highly efficient emulsion separation effect; and the fiber membrane is a porous structure throughout, has excellent water absorption capacity and capillary action, and significantly improves the permeation flux of the nanofiber membrane.
[0009] The first object of the present invention is to provide a method for preparing a biomimetic porous nanofiber emulsion separation membrane, the method comprising the following steps:
[0010] (1) Preparation of PSU / CNC nanofiber membrane
[0011] Add polysulfone (PSU) into an organic solvent to prepare a spinning solution, add a certain amount of biomass nanomaterial cellulose nanocrystals (CNC), heat and stir to obtain a spinning solution, and then electrospin the spinning solution under certain humidity conditions to obtain a PSU / CNC nanofiber membrane;
[0012] (2) Preparation of PSU / CNC-g-AAc nanofiber membrane
[0013] The PSU / CNC nanofiber membrane obtained in step (1) is immersed in a certain concentration of benzophenone (BP) / acrylic acid (AAc) / methanol solution, and irradiated under ultraviolet light for a certain period of time. After the reaction is completed, the grafted membrane is taken out and washed three times with ethanol; then it is immersed in deionized water, taken out and dried to obtain a biomimetic structure porous nanofiber emulsion separation membrane (referred to as PSU / CNC-g-AAc nanofiber membrane).
[0014] In one embodiment, the spinning solution in step (1) is prepared by dissolving PSU in an organic solvent and then adding a certain amount of CNC; wherein PSU accounts for 1-20wt% of the organic solvent and CNC accounts for 1-15wt% of the organic solvent.
[0015] In one embodiment, the organic solvent in step (1) is one or more of acetone (ACE), N,N-dimethylformamide (DMF), and dimethyl sulfoxide (DMSO).
[0016] In one embodiment, the heating and stirring temperature in step (1) is 50-100° C., and the stirring time is 5-15 hours.
[0017] In one embodiment, the process parameters of the electrospinning in step (1) are set as follows: an infusion rate of 0.5 to 3 mL / h, an applied voltage of 10 to 30 kV, an ambient temperature of 10 to 30° C., and a relative humidity of 30 to 90%.
[0018] In one embodiment, in the benzophenone (BP) / acrylic acid (AAc) / methanol solution of step (2), the concentration of the photoinitiator BP is 1 to 10 wt %, and the concentration of the monomer AAc is 10 to 50 wt %.
[0019] In one embodiment, the ultraviolet lamp irradiation time in step (2) is 1 to 30 minutes.
[0020] The second object of the present invention is to provide a bionic structure porous nanofiber emulsion separation membrane prepared by the above method.
[0021] In one embodiment, the nanofibers in the membrane have a spider silk-like spindle knot and are a porous structure throughout; the nanofiber membrane is obtained by electrospinning combined with ultraviolet light irradiation hydrophilic modification; the fiber diameter is nanometer-level, and the spindle knot size is micrometer-level.
[0022] In one embodiment, the spindle knot is obtained by controlling the spinning concentration of polysulfone, and the mass ratio of polysulfone to organic solvent is 1-20wt%; the porous structure is obtained by mixing biomass nanomaterial cellulose nanocrystals with hydrophobic polymer polysulfone, and absorbing moisture and phase separation during the electrostatic spinning process, and the cellulose nanocrystals account for 1-15wt% of the organic solvent.
[0023] In one embodiment, the bionic structure porous nanofiber emulsion separation membrane has a spindle knot that imitates spider silk, which can make the emulsified oil in water move in a directional manner and spontaneously aggregate under the action of Laplace pressure difference, thereby achieving a high-efficiency emulsion separation effect; and the fiber membrane has a porous structure throughout, has excellent water absorption capacity and capillary action, and significantly improves the permeation flux of the nanofiber membrane; the fiber diameter is about 500-800nm, and the major axis size of the spindle knot is about 10-15μm.
[0024] In one embodiment, the average pore size of the bionic structure porous nanofiber emulsion separation membrane is 1.5 to 2.5 μm.
[0025] In one embodiment, the bionic structure porous nanofiber emulsion separation membrane has super hydrophilicity in air, and the wetting time to water is less than 1 s; the underwater oil contact angle of the membrane can reach 150° to 161°.
[0026] In one embodiment, the biomimetic porous nanofiber emulsion separation membrane has high permeation flux and high separation efficiency for various non-polar oils and edible oil water-in-oil emulsions, and the flux can reach 6000L m -2 h -1 Above, the efficiency can reach over 99.3%.
[0027] The present invention also provides application of the bionic structure porous nanofiber emulsion separation membrane in separation of oil-water mixture or oil-water emulsion.
[0028] In one embodiment, the oil phase in the oil-water mixture or the oil-water emulsion can be selected from any one or more of the following: cyclohexane, isooctane, hexadecane, and soybean oil.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] (1) The nanofiber membrane prepared by the present invention has a spindle knot, so that the membrane has a coalescing effect on the emulsified oil, that is, the emulsified oil in water can be directed to move and spontaneously coalesce under the action of Laplace pressure difference, thereby achieving an efficient emulsion separation effect.
[0031] (2) The nanofiber membrane prepared by the present invention has a porous structure throughout, has excellent water absorption capacity and capillary action, and can significantly improve the permeation flux of the nanofiber membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 Microstructure diagrams of PSU / CNC-g-AAc nanofiber membranes prepared in Example 1 and Comparative Example 1; (a) is Example 1; (b) is Comparative Example 1. DETAILED DESCRIPTION
[0033] In order to make the above-mentioned objects, features and advantages of the present invention more clearly understood, the present invention is further described in detail below with reference to examples. However, the present invention is not limited to the examples listed, but also includes any other known changes within the scope of the rights claimed by the present invention.
[0034] The test method involved in the present invention is:
[0035] 1. Morphology: The morphology of the fiber membrane samples was characterized by scanning electron microscopy (FESEM, SU-8010, Hitachi, Japan).
[0036] 2. Pore size: The pore size distribution of the membrane was measured using a capillary flow meter (CFP-1100A, PMI, USA).
[0037] 3. Contact angle: The water contact angle in air and the underwater oil contact angle of the sample were tested at room temperature using a contact angle meter (Powereach JC2000D1). The types of oils were: 1,2-dichloroethane, cyclohexane, isooctane, hexadecane, and soybean oil. Since the underwater oil contact angles of different types of oils are not much different, the present invention mainly uses 1,2-dichloroethane as an example for description.
[0038] 4. Separation performance:
[0039] Preparation of oil-in-water emulsion: Oil and water were mixed in a volume ratio of 1:99, and isooctane oil-in-water emulsion was prepared by ultrasonication at a power of 560 W for 30 min. The average particle size of the emulsified oil in the obtained oil-in-water emulsion was about 1 μm.
[0040] The membrane was placed in a dead-end filtration device for emulsion separation experiments. The membrane permeation flux (J, L m -2 h -1 ) is calculated according to formula (1):
[0041] Permeate flux = filtrate volume / (filtration area × filtration time) (1)
[0042] Then, the filtrate was collected and tested for its total organic carbon content (TOC content, mg L -1 ), the separation efficiency (%) of the membrane is calculated according to formula (2):
[0043]
[0044] The embodiments of the present invention will be described in detail below with reference to specific examples.
[0045] Example 1
[0046] A method for preparing a PSU / CNC-g-AAc nanofiber membrane comprises the following steps:
[0047] (1) 4 g PSU was added to 50 g DMF / ACE (volume ratio 2:1), and 2.5 g CNC was added, and stirred in a 90 °C oil bath for 12 h to obtain a PSU / CNC spinning solution, and then the spinning solution was spun at a perfusion rate of 1.5 mL / h and an applied voltage of 20 kV. The spinning temperature was 25 ± 3 °C and the humidity was 75 ± 3% to obtain a biomimetic porous PSU / CNC nanofiber membrane;
[0048] (2) The PSU / CNC nanofiber membrane prepared in step (1) is immersed in a BP / AAc / methanol solution, wherein the concentration of the BP solution is 2wt% and the concentration of the monomer AAc is 20wt%. After irradiation under ultraviolet light for 10 minutes, a grafted membrane is obtained, which is taken out and washed three times with ethanol; then immersed in deionized water for 24 hours, taken out and dried to obtain a hydrophilic bionic structure porous PSU / CNC-g-AAc nanofiber membrane.
[0049] The PSU / CNC-g-AAc nanofiber membrane prepared in this embodiment has a porous structure throughout. The average diameter of the nanofibers is about 600 nm, the average pore size of the fiber membrane is 1.8 μm, and the long axis size of the spindle knot is about 6.5 μm. The water contact angle of the fiber membrane in the air can quickly spread to 0° within 0.2 s, and the underwater oil contact angle can reach 160.5°. When the fiber membrane is used for the separation of isooctane oil-in-water emulsion, the permeation flux is as high as 6207 L m -2 h -1 , and the separation efficiency is as high as 99.8%.
[0050] Example 2
[0051] A method for preparing a PSU / CNC-g-AAc nanofiber membrane comprises the following steps:
[0052] (1) 4 g PSU was added to 50 g DMF and 2.5 g CNC was added, and the mixture was stirred in a 90 °C oil bath for 12 h to obtain a PSU / CNC spinning solution, and then the spinning solution was spun at a perfusion rate of 2 mL / h and an applied voltage of 18 kV. The spinning temperature was 25 ± 3 °C and the humidity was 75 ± 3% to obtain a bionic structure porous PSU / CNC nanofiber membrane;
[0053] (2) The PSU / CNC nanofiber membrane prepared in step (1) was immersed in a BP / AAc / methanol solution, wherein the concentration of the BP solution was 1 wt % and the concentration of the monomer AAc was 10 wt %. After irradiation under ultraviolet light for 10 min, a grafted membrane was obtained, which was taken out and washed three times with ethanol; then, it was immersed in deionized water for 24 h, taken out and dried to obtain a hydrophilic bionic structure porous PSU / CNC-g-AAc nanofiber membrane.
[0054] The PSU / CNC-g-AAc nanofiber membrane prepared in this embodiment has a porous structure throughout. The average diameter of the nanofibers is about 600 nm, the average pore size of the fiber membrane is 1.7 μm, and the long axis size of the spindle knot is about 6.8 μm. The water contact angle of the fiber membrane in air is 13.8°, and the underwater oil contact angle is 150.1°. When the fiber membrane is used for oil-in-water emulsion separation, the permeation flux of cyclohexane, isooctane, hexadecane, and soybean oil emulsion is low, which is 4983 L m -2 h -1 , the separation efficiency can reach 99.6%.
[0055] Example 3
[0056] A method for preparing a PSU / CNC-g-AAc nanofiber membrane comprises the following steps:
[0057] (1) 3.5 g PSU was added to 50 g DMF, and 2 g CNC was added, and the mixture was stirred in an oil bath at 100 °C for 10 h to obtain a PSU / CNC spinning solution, and then the spinning solution was spun at an infusion rate of 1.8 mL / h and an applied voltage of 23 kV, with a spinning temperature of 23 ± 3 °C and a humidity of 75 ± 3%, to obtain a biomimetic porous PSU / CNC nanofiber membrane;
[0058] (2) The PSU / CNC nanofiber membrane prepared in step (1) is immersed in a BP / AAc / methanol solution, wherein the concentration of the BP solution is 2.5wt% and the concentration of the monomer AAc is 25wt%. After irradiation under ultraviolet light for 15 minutes, a grafted membrane is obtained, which is taken out and washed three times with ethanol; then immersed in deionized water for 24 hours, taken out and dried to obtain a hydrophilic bionic structure porous PSU / CNC-g-AAc nanofiber membrane.
[0059] The PSU / CNC-g-AAc nanofiber membrane prepared in this embodiment has a porous surface structure; the average diameter of its nanofibers is about 500nm, the average pore size of the fiber membrane is 2.1μm, and the long axis size of the spindle knot is about 7.3μm; the water contact angle of the fiber membrane in the air can quickly spread to 0° within 0.1s, and the underwater oil contact angle can reach 160.8°; when the fiber membrane is used for water-in-oil emulsion separation, the permeation flux of cyclohexane, isooctane, hexadecane, and soybean oil emulsion is as high as 6269L m -2 h -1 , the separation efficiency reaches 99.3%.
[0060] Example 4
[0061] A method for preparing a PSU / CNC-g-AAc nanofiber membrane comprises the following steps:
[0062] (1) 6 g of PSU was added to 50 g of DMF, and 3 g of CNC was added, and the mixture was stirred in an oil bath at 100 °C for 10 h to obtain a PSU / CNC spinning solution, and then the spinning solution was spun at a perfusion rate of 2 mL / h and an applied voltage of 20 kV, with a spinning temperature of 23 ± 3 °C and a humidity of 75 ± 3%, to obtain a biomimetic porous PSU / CNC nanofiber membrane;
[0063] (2) The PSU / CNC nanofiber membrane prepared in step (1) is immersed in a BP / AAc / methanol solution, wherein the concentration of the BP solution is 2wt% and the concentration of the monomer AAc is 25wt%. After irradiation under ultraviolet light for 15 minutes, a grafted membrane is obtained, which is taken out and washed three times with ethanol; then immersed in deionized water for 24 hours, taken out and dried to obtain a hydrophilic bionic structure porous PSU / CNC-g-AAc nanofiber membrane.
[0064] The PSU / CNC-g-AAc nanofiber membrane prepared in this embodiment has a porous structure throughout. The average diameter of the nanofibers is about 900 nm, the average pore size of the fiber membrane is 2.0 μm, and there is no spindle knot. The water contact angle of the fiber membrane in the air can quickly spread to 0° within 0.18 s, and the underwater oil contact angle can reach 158.9°. When the fiber membrane is used for oil-in-water emulsion separation, the permeation flux of cyclohexane, isooctane, hexadecane, and soybean oil emulsion is as high as 6033 L m -2 h -1 , the separation efficiency reaches 99.5%.
[0065] Comparative Example 1
[0066] A method for preparing a PSU / CNC-g-AAc nanofiber membrane comprises the following steps:
[0067] (1) 4 g PSU was added to 50 g DMSO and 1 g CNC was added, and the mixture was stirred in an 80 °C oil bath for 12 h to obtain a PSU / CNC spinning solution, and the spinning solution was then spun at a perfusion rate of 1.5 mL / h and an applied voltage of 23 kV. The spinning temperature was 25 ± 3 °C and the humidity was 50 ± 3% to obtain a PSU / CNC nanofiber membrane;
[0068] (2) The PSU / CNC nanofiber membrane prepared in step (1) was immersed in a BP / AAc / methanol solution, wherein the concentration of the BP solution was 1.5wt% and the concentration of the monomer AAc was 15wt%. After irradiation under ultraviolet light for 8 minutes, a grafted membrane was obtained, which was taken out and washed three times with ethanol; then immersed in deionized water for 24 hours, taken out and dried to obtain a hydrophilic bionic structure porous PSU / CNC-g-AAc nanofiber membrane.
[0069] The PSU / CNC-g-AAc nanofiber membrane prepared in this comparative example has a non-porous structure with a smooth fiber surface; the average diameter of the nanofibers is about 1100nm, the average pore size of the fiber membrane is 2.2μm, and there is no spindle knot; the water contact angle of the fiber membrane in the air can quickly spread to 0° within 0.5s, and the underwater oil contact angle can reach 156.5°; when the fiber membrane is used for water-in-oil emulsion separation, the permeation flux of cyclohexane, isooctane, hexadecane, and soybean oil emulsion can reach 5832L m -2 h -1 , the separation efficiency is low, only 83.7%.
[0070] Results
[0071] The nanofiber membranes prepared in Examples 1 to 4 and Comparative Example 1 were applied to oil-water emulsion separation; the preparation of the water-in-oil emulsion was as follows: oil and water were mixed in a volume ratio of 1:99, and isooctane water-in-oil emulsion was prepared by ultrasonication at a power of 560W for 30 minutes. The average particle size of the emulsified oil in the obtained water-in-oil emulsion was about 1 μm. The permeation flux and separation efficiency are shown in Table 1:
[0072] Table 1 Oil-water separation performance of different fiber membranes
[0073] sample <![CDATA[Permeation flux (L m -2 h -1 )]]> Separation efficiency (%) Example 1 6207 99.8 Example 2 4983 99.6 Example 3 6269 99.3 Example 4 6033 99.5 Comparative Example 1 5832 83.7
[0074] The embodiments provided above are not intended to limit the scope of the present invention, and the steps described are not intended to limit the execution order thereof. Those skilled in the art may make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection defined by the claims of the present invention.
Claims
1. A biomimetic porous nanofiber emulsion separation membrane, characterized in that: The nanofibers in the membrane have a spider silk-like spindle knot and are porous throughout; the nanofiber membrane is obtained by electrospinning combined with ultraviolet irradiation hydrophilic modification; the fiber diameter is nanometer-level, and the spindle knot size is micrometer-level; The preparation method comprises the following steps: The spinning solution is prepared by adding polysulfone into an organic solvent, and a certain amount of biomass nanomaterial cellulose nanocrystals is added, and the spinning solution is stirred in an oil bath to obtain the spinning solution, and then the spinning solution is electrospun under certain humidity conditions to obtain a biomimetic porous nanofiber membrane; The bionic structure porous nanofiber membrane is immersed in a benzophenone / acrylic acid / methanol solution and irradiated under ultraviolet light for a certain period of time. After the reaction is completed, a grafted membrane is obtained, which is washed with ethanol; then immersed in deionized water, taken out and dried to obtain a hydrophilic modified bionic structure porous nanofiber membrane.
2. The biomimetic porous nanofiber emulsion separation membrane according to claim 1, characterized in that: The spindle knot is obtained by controlling the spinning concentration of polysulfone, and the mass ratio of polysulfone to organic solvent is 1-20wt%.
3. The biomimetic porous nanofiber emulsion separation membrane according to claim 1, characterized in that: The porous structure is obtained by mixing biomass nano material cellulose nano crystals with hydrophobic polymer polysulfone, and absorbing moisture to cause phase separation during electrostatic spinning, wherein the cellulose nano crystals account for 1-15wt% of the organic solvent.
4. The biomimetic porous nanofiber emulsion separation membrane according to claim 1, characterized in that: The organic solvent is one or more of acetone, N,N-dimethylformamide and dimethyl sulfoxide.
5. The hydrophilic nanofiber membrane according to claim 1, characterized in that: In the benzophenone / acrylic acid / methanol solution, the concentration of benzophenone is 1-10 wt %, and the concentration of acrylic acid is 10-50 wt %.
6. The biomimetic porous nanofiber emulsion separation membrane according to claim 1, characterized in that: The ultraviolet lamp irradiation time is 1 to 30 minutes.
7. The biomimetic porous nanofiber emulsion separation membrane according to any one of claims 1 to 6, characterized in that: The fiber diameter of the bionic structure porous nanofiber emulsion separation membrane is about 500-800 nm, the major axis size of the spindle knot is about 10-15 μm, and the average pore size is 1.5-2.5 μm.
8. The biomimetic porous nanofiber emulsion separation membrane according to any one of claims 1 to 6, characterized in that: The bionic porous nanofiber emulsion separation membrane is super hydrophilic in air and its wetting time to water is less than 1s.
9. The biomimetic porous nanofiber emulsion separation membrane according to any one of claims 1 to 6, characterized in that: The underwater oil contact angle of the bionic structure porous nanofiber emulsion separation membrane can reach 150°~161°.
10. Use of the biomimetic porous nanofiber emulsion separation membrane according to any one of claims 1 to 9 in separation of oil-water mixture or oil-water emulsion.